1985
DOI: 10.1007/bf00964404
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances of synaptosomes isolated from ischemic gerbil brain

Abstract: The effects of cerebral ischemia, induced for 10 min by bilateral common carotid ligation in the Mongolian gerbil, on the brain and synaptosomal content of phospholipids and free fatty acids were measured. Moreover, the incorporation of arachidonic acid and oleoyl-CoA into phospholipids, as well as the respiration and the accumulation of 45Ca, norepinephrine, dopamine, choline, glutamate, and gamma-aminobutyrate in the ischemic brain synaptosomal fraction were studied. Analyses of lipids showed a drop in phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In contrast, some stimulatory effect occurred. Interestingly, this observation complements the finding of Domanska-Janik et al (1985) who have shown that the impaired ability to acylate phospholipids of postischemic synaptosomes was completely abolished if acyl-CoA was used as a substrate. It should be noted, however, that incorporation of the label into synaptic phospholipids from arachidonoyl-CoA was several-fold lower than that when acyl-CoA was generated in situ.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, some stimulatory effect occurred. Interestingly, this observation complements the finding of Domanska-Janik et al (1985) who have shown that the impaired ability to acylate phospholipids of postischemic synaptosomes was completely abolished if acyl-CoA was used as a substrate. It should be noted, however, that incorporation of the label into synaptic phospholipids from arachidonoyl-CoA was several-fold lower than that when acyl-CoA was generated in situ.…”
Section: Discussionsupporting
confidence: 85%
“…This rapid recovery coincides with near complete recovery of the ATP and creatine phosphate levels reported in gerbil brain [1]. It is unclear whether similar mechanisms caused the hyperphosphorylation of the PHF-1 site 3 and 7 days postischemia since sub-normal rather than elevated ATP/ GTP levels have been described in gerbils 3 days after reperfusion [2].…”
Section: Discussionmentioning
confidence: 79%
“…It is followed by the depletion of high-energy phosphates such as creatine phosphate and ATP, an accumulation of lactate, an increase in the intracellular concentration of Ca 2+ , and compromised integrity of the neuronal cytoskeleton [1,2]. Transient global ischemia is associated with shortterm damage occurring within a few hours of blood recirculation and long-term injury induced by multiple factors including oxidative stress [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation